Fantastic contraptions - Isogawa, Yoshihito, 1962- (The LEGO Technic idea book, 2011)
"The book is color throughout, with little to no text accompanying its diagrams ... The LEGO technic idea books are for anyone who wants to create a moving masterpiece, as well as those who want to make original robots with MINDSTORMS. It can also be used to demonstrate how machines work and to experience the fun of mechanics."--Publisher description.